Denok Dance as a Medium Therapy for Mental Disorders of Schizopherenia With a Psychosocial Approach at Soerojo Hospital Magelang Indonesia - Yusril Ihza Mahendra (International Journal of Health and Medicine, 2025)
This research examines the Denok Dance as Therapy for Schizophrenia Mental Disorders through a Psychoanalytic Approach at RSJ Prof Dr. Soerojo Magelang. The aim of the research is to find out the form of dance, the method of dance as therapy and the implementation of Denok dance in the media of therapy for patients with the mental disorder Schizophrenia. The research method is a naturalistic qualitative research method. The data collection process includes observation, interview and documentation techniques. The data validity technique used by researchers is triangulation techniques. The researcher used three stages of data analysis, namely data reduction, data presentation, and conclusion drawing. The results of the research show that the therapy method can increase awareness and emotional stimulation in patients with schizophrenia mental disorders.